STUDIES ON ANTIVIRAL ACTIVITY OF TULSI (OCIMUM SANCTUM) CRUDE EXTRACTS ON SELECTED VIRUSES OF VETERINARY IMPORTANCE - Patil, Usha (International Journal of Ayurveda and Pharma Research, 2018)
Viral diseases are the major causes of devastations in the human history and animal farming worldwide. Bacterial and parasitic diseases have been controlled by use of effective disinfectants, antibiotics and antiparasitic agents. Since, viruses are intracellular and any intervention will affect the cellular metabolism of the host, development of antiviral drugs is a challenge. Drugs acting on microbial agents have been mentioned in Ayurvedic texts as Krimighna Dravyas. Tulsi, Ocimum sanctum is one of the most important medicinal plants mentioned in Ayurvedic literature for its medicinal and spiritual properties. The plant is an highly celebrated medicinal plant as â€œThe incomparable one,â€ â€œMother medicine of natureâ€ and â€œThe queen of herbsâ€. Tulsi, along with other health benefits is known to have anti-infective functions. Hence, antiviral activity of aqueous, ethanol, methanol and chloroform extract of powdered drugs was evaluated against economically important viruses of veterinary importance, Orthmyxovirus and Paramyxovirus. The in vitro cytotoxicity confirmed the safety of the extracts and aqueous extract showed no inhibition on paramyxovirus while showing moderate inhibitory activity on orthomyxovirus while ethanol extract showed moderate inhibitory activity on paramyxovirus and no activity on orthomyxoviruses. Methanol extract showed no inhibition of paramyxovirus while showed significant inhibition of orthomyxovirus. Chloroform extract of the plant showed no inhibition paramyxovirus while significant inhibition was observed on orthomyxoviurs. Results of the study suggest that the O. sanctum can be used as antiviral agent for effective control of viral infections of animal importance.